Correction: A longitudinal cline characterizes the genetic structure of human populations in the Tibetan plateau. - Choongwon Jeong; Benjamin M Peter; Buddha Basnyat; Maniraj Neupane; Cynthia M Beall; Geoff Childs; Sienna R Craig; John Novembre; Anna Di Rienzo (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0175885.].